Evaluation of ORC modules performance adopting commercial plastic heat exchangers. (15th September 2015) - Gómez Aláez, S.L.; Bombarda, P.; Invernizzi, C.M.; Iora, P.; Silva, P.
Highlights: Application of plastic heat exchangers in Organic Rankine Cycle module. Low temperature heat recovery. Design of a 20 kW regenerative ORC adopting commercial plastic heat exchangers. Electricity cost comparable with ORC modules with typical carbon steel components. Economic benefit from plastic evaporator adoption with corrosive heat source media. Abstract: In this paper the possible replacement of conventional metallic heat exchangers with plastic components is investigated with reference to low size Organic Rankine Cycles, aiming at a reduction of the plant investment cost. A thermodynamic optimization of a 20 kW regenerative ORC plant, representative of a low temperature (<140 °C) heat recovery application, has been carried out according to the presently available data for plastic shell and tubes heat exchangers offered on the market. N-heptane was selected as the working fluid, thanks to the capability to operate within the pressure limits for evaporation and condensation processes imposed by the adoption of plastic components. Finally, the potential economic benefit of the plastic solution in comparison with conventional heat exchangers made of carbon steel was evaluated for the whole plant; the case of enhanced materials adoption, which is mandatory for the evaporator in presence of corrosive heat source media, was also considered. It turns out that advantages of the proposed solution become appreciable whenever the presence of corrosive heat source media requires the use of materials other than carbon steel. For instance, for a plant availability of 5000 h/year and discount rate of 10%, we obtain a cost of the produced electricity of 94.8 $/MW h, 95.4 $/MW h, 101.5 $/MW h, and 118.9 $/MW h respectively for plastic, carbon steel, stainless steel and titanium solutions.